The Instructional Text like a Textual Genre - Marinello, Adiane Fogali (2011)
This article analyses the instructional text as a textual genre and is part of the research called Reading and text production from the textual genre perspective, done at Universidade de Caxias do Sul, Campus Universitário da Região dos Vinhedos. Firstly, some theoretical assumptions about textual genre are presented, then, the instructional text is characterized. After that an instructional text is analyzed and, finally, some activities related to reading and writing of the mentioned genre directed to High School and University students are suggested.